2010
DOI: 10.1103/physrevb.81.205445
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport in disordered graphene exposed to ozone: From weak to strong localization

Abstract: We present a magnetotransport study of graphene samples into which a mild disorder was introduced by exposure to ozone. Unlike the conductivity of pristine graphene, the conductivity of graphene samples exposed to ozone becomes very sensitive to temperature: it decreases by more than three orders of magnitude between 100 and 1 K. By varying either an external gate voltage or temperature, we continuously tune the transport properties from the weak to the strong localization regime. We show that the transition o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
128
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 48 publications
19
128
3
1
Order By: Relevance
“…This T -1 dependence indicates that the electron-electron scattering process is the dominant dephasing mechanism in sample A [74]. The intervalley scattering length (l i = (D i ) 1/2 and intravalley scattering length (l * = (D * ) 1/2 ) are ~ 100 nm and they are temperature independent, consistent with previous work [44,47,[73][74][75][76][77][78][79][80]. Having studied the weak-localization phenomenon at low B fields, we now concentrate on the zero B field conductivity data.…”
Section: Electron-electron Interaction In High Quality Epitaxial Grapsupporting
confidence: 76%
See 1 more Smart Citation
“…This T -1 dependence indicates that the electron-electron scattering process is the dominant dephasing mechanism in sample A [74]. The intervalley scattering length (l i = (D i ) 1/2 and intravalley scattering length (l * = (D * ) 1/2 ) are ~ 100 nm and they are temperature independent, consistent with previous work [44,47,[73][74][75][76][77][78][79][80]. Having studied the weak-localization phenomenon at low B fields, we now concentrate on the zero B field conductivity data.…”
Section: Electron-electron Interaction In High Quality Epitaxial Grapsupporting
confidence: 76%
“…By T = 12.5 K, UCF almost disappears in this sample. WL in graphene has been reported in previous studies [44,47,[73][74][75][76][77][78][79][80] and is shown to be due to the quantum interference effect of impurity scattering [51]. Figure 28 .…”
Section: Electron-electron Interaction In High Quality Epitaxial Grapmentioning
confidence: 99%
“…The anomalous magnetoresistance in graphene is the subject of intensive experimental [4][5][6][7][8][9][10][11] and theoretical 12-18 study during the last few years. It was experimentally shown that increasing the carrier density and decreasing the temperature leads to a transition from weak antilocalization to weak localization in graphene.…”
Section: 2mentioning
confidence: 99%
“…However, despite the large amount of disorder, such graphene flakes usually maintain a finite conductivity down to very low temperatures (when deposited onto oxide substrates) owing to electron-hole puddles (charge inohomogeneities fluctuations)-induced percolation effects which limit localization phenomena [2]. The predicted Anderson localization in two-dimensional disordered graphene has been hard to measure in non intentionally damaged graphene, in contrast to chemically modified graphene [230,231]. In a recent experiment, it was however possible to screen out electronholes puddles using sandwiched graphene in between two boron-nitride layers, together with an additional graphene control layer [113].…”
Section: Transport Properties Of Amorphous Graphene 441 Introductionmentioning
confidence: 99%